Attitude of farmers towards Pangas farming for their livelihood improvement (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was conducted in the selected Malotipur village of Muktagachha upazila under Mymensingh district during 13 to 28 April, 2014. The sample size of the study was 90 fish farmers (43 percent of population) and it was drown from a population of 209 using simple random sampling technique. Eight (8) selected characteristics of farmers viz.: age, level of education, family size, farm size, annual income, credit received, training experience and cosmopoliteness were considered as the independent variables, while the attitude of the farmers towards Pangas farming was the dependent variable of the study. The focus variable i.e. attitude of farmers towards Pangas farming was measured with a 5 point likert scale such as ‘strongly agree’, ‘agree’, ‘undecided’, ‘disagree’ and ‘strongly disagree’ in Pangas farming and the corresponding scores were 5, 4, 3, 2 and 1 respectively. The findings indicated that the majority (50 percent) of the Pangas farmers had moderately favorable attitude towards Pangas farming compared to 31.1 percent having highly favorable and only 18.9 percent had slightly favorable attitude. The finding on problem faced by the farmers related to Pangas farming revealed that about two-third (65.6 percent) of the farmers had high problem followed by 20 percent low problems. Among eight selected characteristics of Pangas farmers five characteristics such as age, level of education; annual income, training experience and cosmopoliteness had significant positive relationships with their attitude towards Pangas farming. On the other hand, the other two characteristics of pangas farmers such as family size and farm size had positive but no significant relationships with their attitude towards Pangas farming.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 106-119